2021
DOI: 10.1093/tbm/ibab034
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a workplace physical activity intervention in child care: process evaluation results from the Care2BWell trial

Abstract: Care2BWell was designed to evaluate the efficacy of Healthy Lifestyles (HL), a worksite health promotion intervention to increase child care workers’ physical activity. The purpose of this study was to use process evaluation to describe the implementation of HL and determine if different levels of implementation are associated with changes in workers’ physical activity. Data were collected from 250 workers randomized to HL, a 6 month, multilevel intervention that included an educational workshop followed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…nutrition, physical activity) and did not include explicit focus on peer support. 4,5 Data from the first three cohorts of the program further underscored FCC providers' need for health promotion. Providers struggle with nutrition, physical activity and stress levels that contribute to their overall wellbeing and can influence their ability to provide high quality care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…nutrition, physical activity) and did not include explicit focus on peer support. 4,5 Data from the first three cohorts of the program further underscored FCC providers' need for health promotion. Providers struggle with nutrition, physical activity and stress levels that contribute to their overall wellbeing and can influence their ability to provide high quality care.…”
Section: Discussionmentioning
confidence: 99%
“…Process evaluation data from an initial study showed that implementation varied significantly across sites and no improvements in physical activity were observed in participants. 4 The Create Health Futures program, a web-based intervention focused on healthy eating among ECE professionals, had no significant impact on diet quality or dietary behaviors. 5 In contrast, the Cultivating Healthy Intentional Mindful Educators (CHIME) program, which focuses on the social-emotional health of ECE professionals, has been shown to increase emotional wellbeing and mindfulness in pilot studies.…”
Section: Introductionmentioning
confidence: 96%